Eksplorasi Pertemanan (Circle) terhadap Perkembangan Empati dan Keterampilan Sosial Remaja di MTsN 1 Pamekasan - Ahmad Hafid; Iswatun Hasanah (Universitas Islam Negeri (UIN) Salatiga, 2026)
This study aims to explore friendship circles and their impact on the development of empathy and social skills, as well as the factors influencing them among adolescents at MTsN 1 Pamekasan. The study employs a qualitative approach with an exploratory-descriptive design. Data were collected through non-participant observation, in-depth interviews with students, Guidance and Counseling teachers, and homeroom teachers, as well as documentation. The research informants consisted of 15 students representing various friendship circles, 1 Guidance and Counseling teacher, and 3 homeroom teachers. The findings identified three main types of friendship circles: academic circles, extracurricular circles, and general social circles based on shared gender or habits. Friendship circles have dual effects; positive circles enhance empathy, collaboration, and effective communication, while negative circles reduce empathy and lead to social withdrawal. Influencing factors include gender similarity, shared activities, and the presence of a dominant figure. This study concludes that friendship circles are a crucial determinant of adolescents’ social-emotional development. The implications emphasize the need for group counseling services based on Islamic values to guide students in building healthy friendships.